Radio haloes of star-forming galaxies. Issue 2 (23rd December 2019) - Vijayan, Aditi; Nath, Biman B; Sharma, Prateek; Shchekinov, Yuri
ABSTRACT: We study the synchrotron radio emission from extra-planar regions of star-forming galaxies. We use ideal magnetohydrodynamic simulations of a rotating Milky Way-type disc galaxy with distributed star formation sites for three star formation rates (0.3, 3, 30 M⊙ yr −1 ). From our simulations, we see emergence of galactic-scale magnetized outflows, carrying gas from the disc. We compare the morphology of the outflowing gas with hydrodynamic simulations. We look at the spatial distribution of magnetic field in the outflows. Assuming that a certain fraction of gas energy density is converted into cosmic ray energy density, and using information about the magnetic field, we obtain synchrotron emissivity throughout the simulation domain. We generate the surface brightness maps at 1.4 GHz. The outflows are more extended in the vertical direction than radial and hence have an oblate shape. We further find that the matter right behind the outer shock shines brighter in these maps than that above or below. To understand whether this feature can be observed, we produce vertical intensity profiles. We convolve the vertical intensity profile with the typical beam sizes of radio telescopes, for a galaxy located at 10 Mpc to estimate the radio scale height and compare with observations. The radio scale height is ∼300–1200 pc, depending on the resolution of the telescope. We relate the advection speed of the outer shock with the surface density of star formation as v_adv Σ _SFR^0.3, which is consistent with earlier observations and analytical estimates.